Development of a counseling intervention protocol to improve treatment adherence of ischemic heart disease patients - Chandima Kumara Walpita Gamage; Piyanjali Thamesha de Zoysa; Aindralal Balasuriya; Neil Francis Joseph Fernando (Asian Journal of Medical Sciences, 2022)
Background: Ischemic heart disease (IHD) has been identified as the foremost cause of morbidity and mortality in Sri Lanka. Aims and Objectives: The main aim of this study was to develop a socio-culturally appropriate health counseling intervention protocol to enhance the adherence of prescribed physical activity, diet, and medication among IHD patients attending medical clinics in Sri Lanka. Materials and Methods: This protocol was designed to be used by health professionals and consisted of two sections – an assessment and an intervention. The intervention section integrated communication skills with motivational interviewing, goal setting, and problem-solving. A panel of five experts reviewed each section of the protocol, in a Delphi process. The ratings received at Delphi stage one that was evaluated for degree of consensus. The protocol was modified according to the comments received and resent for a second Delphi round. Again, the re-ratings were reevaluated for the degree of consensus. With regard to assessing consensus, each section was revised/removed if 70% or more of the re-ratings were at 0–3 and kept as the same if 70% or more of the re-ratings were at four or above. Results: All the subsections were rated in categories of four and above in both stages. Therefore, none of the sections was removed from the original protocol. Some modifications were done according to the suggestions received in the Delphi review. Conclusion: The finalized protocol would be initially implemented in selected hospitals in Galle district as a quasi-experimental study in the near future.